Nondestructive maturity assessment tools for commercially viable fruits and vegetables in Uganda - Okiror, Paul; Lejju, Julius Bunny; Bahati, Joseph; Rugunda, Kagoro Grace; Sebuuwufu, Collins Inno (African Journal of Plant Science, 2017)
Fruit and vegetable maturity at harvest influences transportation and storage requirements as well as market value. However, small scale farmers in Uganda lack technologies for maturity assessment leading to high pre- and post-harvest losses and low financial returns from fruit and vegetable farms. This study, therefore, assessed the development of fruits (pineapple, passion fruit, watermelon) and vegetables (cabbage, egg plant, pumpkin and tomato), determined optimal maturity indices and fabricated and tested nondestructive tools for maturity assessment. Propagation trials and testing of tools were undertaken at Nangabo and Kangulumira sub counties in central Uganda. The findings show that eggplant, passion fruit, pineapple and pumpkin underwent 3 distinct development stages during which their diameter, length and outer colour changed. Cabbage remained green, but its bulb diameter and length varied with maturity. Watermelon had 4 development stages with significant (P≤0.05) changes in morphology and outer colour. Tomato fruits had 6 distinct outer colour changes. Age and colour were maturity indices for passion fruit. Fruit age and diameter were the maturity indices for watermelon. Age, diameter, length and colour were the maturity indices for pineapple, tomato and eggplant. Cabbage and pumpkin share indices including: age, diameter and length. A farm record book (FRB) was designed for documenting phenology and maturity stages of studied fruits and vegetables. A calibrated calliper (CC) and Calibrated tape (CT) were fabricated for assessing the morphological development in pineapple, tomato, eggplant, cabbage, pumpkin and watermelon. Customized colour charts (CCC) were designed for monitoring colour changes as passion fruits, pineapples, tomatoes and eggplants mature. On-farm trials show that CCCs were the most effective tools for monitoring passion fruit (80%), pineapple (64%), tomato (60%), eggplant (68%). Similar studies involving several cultivars and maturity determination tools are, therefore, recommended.
Keywords: Fruit; Kangulumira; Maturity index; Maturity determination tools; Nangabo; Vegetable